Teaching in Mixed Aged Classes in Small Rural Schools - Raggl, Andrea (Swiss Journal of Educational Research, 2012)
The characteristics of «small schools» are described in this paper together with the teaching and learning practices in mixed aged classes of rural-alpine schools. In these rural areas, mixed age classes are mainly an organizational measure to keep schools with a low number of pupils open. However, teachers and headteachers involved in the research project «Schools in alpine regions» also celebrate the pedagogical advantages of small schools and mixed aged learning. Some of them take advantage of their autonomy to develop innovative teaching and learning practices. Yet, the research also shows that mixed age classes involve important challenges for teachers, especially for those in very small ‘one-teacher-schools’.